Influence of Loading and Unloading Effect on Bearing Capacity of Pile Tip. Issue 3 (September 2019) - Ma, Hailong; Lei, Shanshan; Yang, Bilian; Ma, Yufei; Chen, Haibing
Abstract: The upper pile of the O-cell test pile has an unloading effect on the soil around the pile, resulting in the pile tip resistance being lower than the top-loaded pile. In order to solve this problem, the Mindlin formula is used to calculate the additional stress caused by the lateral friction resistance at the pile tip. Then introduce this additional stress into the Meyerhof ultimate tip resistance formula and obtain an improved formula for calculating the pile tip resistance. The improved formula can fully consider the influence of different loading directions on the pile tip resistance. The top-loaded pile has a loading effect on the pile tip soil, and the bottom-supported pile has the unloading effect on the pile tip soil. The example verification shows that the pile tip resistance of top-loaded pile and O-cell test pile calculated by the modified Meyerhof tip resistance formula are close to the measured values. The improved formula is of great significance for further study of the effect of the loading and unloading effect on the pile tip resistance.